PENINGKATAN KEMAMPUAN MENGURUTKAN (SERIASI) MELALUI MEDIA RODA PUTAR PADA ANAK KELOMPOK B TK NEGERI PEMBINA SUNGAI PINANG - Rina Kurnia; Akbari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve children's sequencing (seriation) abilities through the use of a spinning wheel media in Group B at TK Negeri Pembina Sungai Pinang. This research is a Classroom Action Research using the Kemmis and McTaggart model, which consists of four stages (planning, implementation, observation, and reflection). The subjects of this study were children in Group B1, totaling 16 children, consisting of 8 boys and 8 girls. The object studied was children's sequencing (seriation) abilities through the spinning wheel media. Data collection was conducted through observation and documentation. The data analysis technique used qualitative and quantitative analysis. The results of the study showed that the use of spinning wheel media could improve children's sequencing (seriation) abilities. This improvement can be seen from the initial condition in which the sequencing (seriation) abilities of Group B1 children were in the very well-developed category (BSB) before the action was carried out reaching 6.25%, increasing to 18.75% in cycle I, and further rising to 81.25% in cycle II. Keywords : Early Childhood Education, Sequencing (Seriation), Spinning Wheel Media